2018
DOI: 10.1038/s41439-018-0023-9
|View full text |Cite
|
Sign up to set email alerts
|

Sensorineural hearing loss and mild cardiac phenotype caused by an EYA4 mutation

Abstract: EYA4 is a member of the vertebrate eya gene family of transcriptional activators and plays several roles in both embryonic and inner ear development. The majority of EYA4 gene mutations are associated with autosomal dominant non-syndromic hearing loss (DFNA10). In addition, some mutations in this gene cause autosomal dominant syndromic hearing loss with dilated cardiomyopathy. EYA4 is a rare cause of sensorineural hearing loss, and only a limited number of papers regarding mutations in this gene have been publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 15 publications
(21 reference statements)
0
14
0
Order By: Relevance
“…Nevertheless, in human studies, genetic variation in a shared set of genes has been shown to confer risk to both cardiovascular disease and HL independently. EYA4 mutations have been reported in persons with SNHL preceding dilated cardiomyopathy by 1 to 2 decades and multiple kindreds with SNHL alone 41–43 . SNPs in EYA4 independently have been implicated in GWAS on atrial fibrillation and HL 16,44 .…”
Section: Cardiovascular Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, in human studies, genetic variation in a shared set of genes has been shown to confer risk to both cardiovascular disease and HL independently. EYA4 mutations have been reported in persons with SNHL preceding dilated cardiomyopathy by 1 to 2 decades and multiple kindreds with SNHL alone 41–43 . SNPs in EYA4 independently have been implicated in GWAS on atrial fibrillation and HL 16,44 .…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…Traditionally, cardiovascular abnormalities are thought to be related to congenital syndromic forms of HL. These syndromes include Jervell and Lange-Nielsen [41][42][43] SNPs in EYA4 independently have been implicated in GWAS on atrial fibrillation and HL. 16,44 Genetic variations in genes related to homocysteine metabolism including MTHFR are associated with susceptibility to age-related HL.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…1F ). EYA4 , a gene associated with hearing loss and cardiomyopathy(Abe et al, 2018), was over-expressed in older individuals regardless of cancer status in four out of six tissue types. Similarly, HENMT1, NOA1 , and ZNF518B were over-expressed in younger individuals in three out of six tissue types.…”
Section: Resultsmentioning
confidence: 99%
“…Truncating EYA4 mutations cause late-onset autosomal dominant dilated cardiomyopathy. However, the patients with EYA4 mutations were characterized by progressive and late-onset in reported cases [ 13 , 14 ]. Thus, the relationship between the disruption of EYA4 gene and CHD phenotypes in our case is still need to be further studied.…”
Section: Discussionmentioning
confidence: 99%